LOW-DENSITY LIPOPROTEIN SUBFRACTIONS AND VARYING DEGREE OF CORONARY STENOSIS - I. N. Ozerova; N. V. Perova; V. A. Metelskaya; O. I. Chernushevich; N. E. Gavrilova (Кардиоваскулярная терапия и профилактика)
Aim. To investigate whether low and intermediate density lipoprotein (LDL, IDL) subfractions are associated with a degree of angiographically verified coronary atherosclerosis, as well as with other biochemical risk factors of coronary heart disease (CHD), and hypertriglyceridemia (HTG) in particular.Material and methods. The study included 129 patients (76 men and 53 women), aged 33–75 years, who were referred for coronary angiography. All participants were divided into three groups by the degree of coronary artery (CA) stenosis: 0–20%, 21–70%, and >70%. LDL and IDL subfractions were measured with the Lipoprint LDL System (electrophoresis in 3% polyacrylamide gel).Results. All groups were similar by the levels of lipid and apoprotein parameters. The levels of high-sensitive C-reactive protein and glucose, as well as HOMA-IR index, were higher in Group 3 patients. In most cases of severe CA stenosis, small dense LDL particles were detected. In HTG patients, higher levels of small dense LDL3 particles were registered only together with the CA stenosis of at least 21–70%.Conclusion. The findings on lipoprotein subfractions, obtained with the Lipoprint LDL System, have demonstrated that in patients with verified coronary atherosclerosis, there is a link between the levels of more atherogenic small dense LDL3 particles, the degree of CA stenosis, and blood TG levels. The combination of HTG and high LDL3 levels could be considered an additional marker of severe CA atherosclerosis.